2016
DOI: 10.1186/s13568-015-0171-y
|View full text |Cite
|
Sign up to set email alerts
|

Accessing inoculation methods of maize and wheat with Azospirillum brasilense

Abstract: The utilization of inoculants containing Azospirillum is becoming more popular due to increasing reports of expressive gains in grain yields. However, incompatibility with pesticides used in seed treatments represents a main limitation for a successful inoculation. Therefore, in this study we searched for alternatives methods for seed inoculation of maize and wheat, aiming to avoid the direct contact of bacteria with pesticides. Different doses of inoculants containing Azospirillum brasilense were employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
108
2
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(160 citation statements)
references
References 52 publications
8
108
2
18
Order By: Relevance
“…As variáveis número de perfilhos, número de grãos por espiga e massa de mil grãos não apresentaram diferenças significativas entre os tratamentos, indicando não haver efeito da inoculação, associada ou não à adubação nitrogenada, nestes parâmetros da cultura. Por outro lado, Fukami et al (2016) observaram maior perfilhamento em trigo quando da inoculação das sementes, e destacaram que esse aumento pode ser considerado um dos mecanismos de promoção no rendimento em resposta à inoculação. Avaliando a inoculação com Azospirillum brasilense associada à aplicação de N mineral, Lemos et al (2013) obtiveram as maiores médias de grãos por espiga no trigo com a aplicações de N e/ou com N mais o inoculante.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…As variáveis número de perfilhos, número de grãos por espiga e massa de mil grãos não apresentaram diferenças significativas entre os tratamentos, indicando não haver efeito da inoculação, associada ou não à adubação nitrogenada, nestes parâmetros da cultura. Por outro lado, Fukami et al (2016) observaram maior perfilhamento em trigo quando da inoculação das sementes, e destacaram que esse aumento pode ser considerado um dos mecanismos de promoção no rendimento em resposta à inoculação. Avaliando a inoculação com Azospirillum brasilense associada à aplicação de N mineral, Lemos et al (2013) obtiveram as maiores médias de grãos por espiga no trigo com a aplicações de N e/ou com N mais o inoculante.…”
Section: Resultsunclassified
“…Outros estudos encontraram resultados semelhantes (HUNGRIA et al, 2010;HUNGRIA, 2011), o que ajuda a reforçar a possibilidade de redução das quantidades de N aplicadas em cobertura quando é feita a inoculação das sementes. Fukami et al (2016) destacam que a substituição total da adubação nitrogenada pela inoculação pode não ser viável, contudo, a inoculação permite uma redução de cerca de 25% do N a ser aplicado na cultura.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…is also being increasingly adopted in several countries, especially for crops such as corn and wheat (Díaz-Zorita & Fernandez-Canigia, 2009;Hartmann & Bashan, 2009;Marks et al, 2015). The analysis of results from a large number of field trials with various non-legume crops, conducted worldwide over 20 years, under different soil and weather conditions, has demonstrated that yield increases of up to 30% could be obtained 70% of the time (Fukami et al, 2016;Fukami et al, 2017) in response to inoculation with Azospirillum.…”
Section: Introductionmentioning
confidence: 99%